Midwifery education in Central-Eastern Europe - Mivšek, Polona; Baškova, Martina; Wilhelmova, Radka (Midwifery, 2016)
Problems in midwifery in many Central-Eastern European countries are very similar; it is possible to speak about the evolving Central-Eastern model of midwifery care. The educational models of this region have a relatively strong theoretical part; however, there is an insufficient practical dimension. Theoretical part of midwifery education in the universities is relatively autonomous and is slowly changing the professional identity of graduates.
Keywords: Midwifery; vzdělávací modely; European Union; kurikulum; služby zdravotní péče o matku; Curriculum; role odborníka; Surveys and Questionnaires; Models, Educational; Professional Role; Evropská unie; Professional identity; Autonomy; průzkumy a dotazníky; porodní asistentky; Nurse Midwives; východní Evropa; Midwifery education in central-east Europe; Maternal Health Services; babictví; Europe, Eastern